Educating air forces : global perspectives on airpower learning - Wakelam, Randall T. (Randall Thomas), 1953-; Varey, David, 1966-; Sica, Emanuele, 1975- (Aviation & air power, 2020)
"Compared to armies and navies, which have existed as professional fighting services for centuries, the technology that makes air forces possible is much newer. As a result, these services have had to quickly develop methods of preparing aviators to operate in conditions ranging from peace or routine security to full-scale war. The first book to address the history and scope of air power professionalization through learning programs, Educating Air Forces offers valuable new insight into strategy and tactics worldwide. Here, a group of international experts examine the philosophies, policies, and practices of air service educational efforts in the United States, France, Italy, Germany, Australia, Canada, and the UK. First, the contributors discuss the founding, successes, and failures of European air force learning programs between the Great War and World War II. Chapters in section two explore how the tense political climate during the Cold War influenced the creation, curriculum, and results of various programs. The final section addresses the post-Cold War era, specifically examining how educational programs are adapting to soldiers' needs and the demands of modern warfare. Featuring contributions from eminent scholars in the field, this volume surveys the learning approaches globally employed by air forces in the past century and evaluates their effectiveness. Educating Air Forces reveals how experiential learning and formal education are not only inextricably intertwined, but also necessary to cope with advances in modern warfare"--